Chlamydial infection, plasma peroxidation and obesity in tubal infertility (2011)
Background: Genital tract infections and obesity are both sources of oxidative stress. Alterations in immune and antioxidant parameters may arise from this or from an indeterminate autoimmune mechanism. Objective: This study aimed to investigate the association of Chlamydial infection, obesity and oxidative response with tubal infertility in Nigerian women. Methods: It was a case-control study of 40 women with tubal infertility and 32 fertile women, respectively, recruited from the Infertility and Family Planning Clinics respectively, of the University College Hospital, Ibadan, Nigeria. Anthropometric indices were measured in each subject and endocervical swabs were taken to screen for current genital tract infection. Antioxidant, hormonal and immunologic analysis were performed on serum. Results: None of the subjects had current genital tract infections. Chlamydia trachomatis IgG positivity was significantly higher in infertile than in fertile subjects [OR 4.33; 95%CI (0.078-0.681)]. No significant variations were observed in the anthropometric indices, antioxidant parameters and hormones between infertile and the fertile women. Body mass index correlated positively with oxidative stress in infertile subjects. Waist and hip circumferences correlated negatively with oestradiol in women with tubal infertility. Conclusion: Chlamydial infection is associated with tubal factor infertility, however, obesity seems to increase oxidative stress and reduce fertility potential in women with tubal factor infertility.